Transformasi Perpustakaan Berbasis Inklusi Sosial Terhadap Kesejahteraan Masyarakat di Dinas Perpustakaan Kota Sibolga - Muhammad Rifky Fansuri; Abdul Karim Batubara (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This journal discusses the importance of social inclusion-based library transformation in improving community welfare. The background of this research is the social inclusion-based library transformation program initiated by the Head of the National Library of the Republic of Indonesia. Social inclusion-based libraries provide facilities to the community to develop their potential to improve welfare in various fields. The research was conducted using a qualitative approach involving the Sibolga City Library, Indonesia. In this study, it was found that the transformation of libraries into social inclusion can help communities gain access to information, learning opportunities, and community empowerment. In addition, library transformation can also increase community participation in library activities and help build positive social relationships. This study also shows that library transformation based on social inclusion can improve community well-being in several aspects, such as skills development, literacy, mental health, and cultural identity. However, the challenges faced in the library transformation process are lack of funding, lack of support from the government, and lack of public awareness about the benefits of the library itself. For this reason, government and community support is essential in encouraging the transformation of libraries to be more inclusive and provide better services for the community. Overall, library transformation based on social inclusion can help improve community welfare through access to information, learning opportunities, and overall community empowerment.